Performance of Small and Medium Enterprises in Indonesia Impacted by Financial Accessibility - Rusliana, Nanang; Alisjahbana, Armida Salsiah; Budiono, Budiono; Purnagunawan, Raden Muhamad (Muhammadiyah University Press, 2023)
The goals of this study are to examine and analyze the financial accessibility of SMEs in Indonesia, to examine the impact of financial constraints on SMEs’ performance there, and to determine how SMEs’ performance in Indonesia is impacted by their involvement in the financial market. This analysis makes use of panel data from the 2009 and 2015 waves of the World Bank Enterprise Survey (ESWB). Quantitative analysis with panel data regression models utilizing the Fixed Effect Model (FEM) or Random Effect Model (REM) and Hausman test constitute the analytical framework for this study. Stata Software is used for all computations and estimation related to the model and its tests. The results show that financial accessibility has a greater influence on sales growth compared to labor growth in medium-sized businesses, while in small businesses financial accessibility has a smaller effect on sales growth compared to labor growth. The number of small companies that are not financially constrained is more than the number of companies participating in the financial market. And participation in the financial market has an influence on business performance, both in terms of sales growth and workforce growth.